The Psychobiological Model: Towards a New Theory of Computer-Mediated Communication Based on Darwinian Evolution - Kock, Ned (Organization Science, 2004)
This article reviews theories of organizational communication with a special emphasis on theories that have been used to explain computer-mediated communication phenomena. Among the theories reviewed, two—social presence and media richness—are identified as problematic and as posing obstacles to future theoretical development. While shortcomings of these theories have been identified in the past, some of these theories' predictions have been supported by empirical evidence. It is argued that this theoretical dilemma can be resolved based upon principles derived from a modern version of Darwin's theory of evolution by natural selection and the application of those principles to the understanding of human evolution. A new theoretical model called the psychobiological model is developed, which predicts variations in cognitive effort in computer-mediated collaborative tasks. The model proposes that there is a negative causal link between the “naturalness” of a computer-mediated communication medium, which is the similarity of the medium to the face-to-face medium, and the cognitive effort required from an individual using the medium for knowledge transfer. The model also states that this link is counterbalanced by what are referred to as “schema alignment” and “cognitive adaptation.” The schema alignment construct refers to the similarity between the mental schemas of an individual and those of other participant(s). The cognitive adaptation construct refers to an individual's level of schema development associated with the use of a particular medium. Finally, the model states that the degree to which the medium supports an individual's ability to convey and listen to speech is particularly significant in defining its naturalness, more so than the medium's degree of support for the use of facial expressions and body language. An example is offered of how the psychobiological model can be tested in the context provided by the customer support area of an online broker.